2009
DOI: 10.1098/rspb.2009.0369
|View full text |Cite
|
Sign up to set email alerts
|

Growing with siblings: a common ground for cooperation or for fiercer competition among plants?

Abstract: Recent work has shown that certain plants can identify their kin in competitive settings through root recognition, and react by decreasing root growth when competing with relatives. Although this may be a necessary step in kin selection, no clear associated improvement in individual or group fitness has been reported to qualify as such. We designed an experiment to address whether genetic relatedness between neighbouring plants affects individual or group fitness in artificial populations. Seeds of Lupinus ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 60 publications
(84 reference statements)
3
75
1
3
Order By: Relevance
“…However, recent studies have shown that the competition between plants is more complicated than previously thought (Chu et al 2008;Milla et al 2009). Dudley and File (2007) demonstrate that Cakile edentula increases allocation to roots to increase competition when two individuals are strangers (from different mother plants of the same species), but not when they are siblings (from the same mother plants).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, recent studies have shown that the competition between plants is more complicated than previously thought (Chu et al 2008;Milla et al 2009). Dudley and File (2007) demonstrate that Cakile edentula increases allocation to roots to increase competition when two individuals are strangers (from different mother plants of the same species), but not when they are siblings (from the same mother plants).…”
Section: Introductionmentioning
confidence: 96%
“…Initially, many studies have measured effects of growing with siblings or strangers on fitness (Cheplick and Kane 2004;Milla et al 2009) to understand mechanisms of kin selection and resource partitioning. Subsequently, some studies have investigated effects of growth with siblings or strangers on morphological and allocation traits (Dudley and File 2007;Murphy and Dudley 2009;.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable feature of these performance comparisons in plants is the variation in results, with positive, negative, and no fitness benefits to growing with siblings compared with strangers (reviewed in Milla et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This idea plays a key role in hypotheses for the evolution of sex [3,4] and outcrossing [5] and has received some support in plant ecology (e.g. [6][7][8] and references therein).…”
Section: Introductionmentioning
confidence: 99%